The influence of governance to zakat disbursement efficiency : empirical evidence from Brunei Darussalam - Nurul Nabilah binti Haji Ali (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
The study measures and analyses zakat disbursement efficiency for the zakat institution in Brunei Darussalam and identifies the governance factor(s) that influence efficiency. This research samples four districts of Brunei Darussalam: Brunei Muara, Belait, Tutong, and Temburong. This is a quantitative research study that uses two approaches of efficiency analysis, namely (i) zakat disbursement efficiency measurement (ratio analysis) and (ii) identification of governance factor(s) that influence the zakat disbursement efficiency of the zakat institutions (regression analysis). In the first approach, there are three efficiency measures namely Disbursement Efficiency (DE), Cost Efficiency (CE) and Time Efficiency (TE). The first findings discover that on average, Tutong is the most efficient district as it has the highest in disbursement and cost efficiency but lowest in time efficiency. Meanwhile, Temburong is the least efficient district as it has the lowest in cost and second lowest in time efficiency. The second finding found that for the past 13 years all districts have showed fluctuations in efficiency in cost, disbursement and time. In terms of disbursement efficiency, the most improved district within the thirteen years of study is Tutong with 69.4% and the least improved district is Brunei Muara with 47.2%. As per cost efficiency, the most improved district is Temburong with 204%. Nevertheless, other districts have discovered no improvement. In time efficiency, Temburong is the most improved district with 11.04%. However, other districts have showed no improvement from the year 2000. In the second approach, there are governance factors namely (i) board size; (ii) professionals on board and (iii) frequency of board meetings.to identify the influence of governance factors onto zakat disbursement efficiency measures. The factors are namely (i) Board Size; (ii) Professionals on Board and (iii) Frequency of Board Meetings. The third findings found that there is a positive influence between Board size and disbursement efficiency and negative influence with cost and time efficiency; professionals on the board has a positive influence to disbursement, cost and time efficiency and lastly, the frequency of board meetings positively influences disbursement efficiency and time efficiency. Frequency of board meetings showed a negative influence with cost efficiency. However, the result between frequency of board meetings and cost and time efficiency are rejected because of insignificant result. This research examines how the zakat institution in Brunei has improved in terms of disbursement activities over the past 13 years. Besides that, this research is significant as it could be useful in future discussions on the potential ways to improve zakat governance and efficiency in Brunei Darussalam. The outcomes from the discussions will be useful as a guide to policymakers in improving the zakat institution's governance system.